Developing Management and Leadership Training Innovation Program for Higher Education at Muhammadiyah Universities - Muh Samsudin; Sadam Fajar Shodiq; Nanan Abdul Manan; Widia Nur Jannah; Wachidi Wachidi; Rusdarti Rusdarti; Mustofa Dasuki (Universitas Muhammadiyah Surakarta, 2022)
The management and leadership training innovation model used by Muhammadiyah universities according to the principles of good instructional development is not yet available. The aims of this research are (1) to describe the appropriate management and leadership training for university leaders at Muhammadiyah universities today; (2) to identify current approaches to management and leadership training; (3) to develop suitable management and leadership training packages for leaders; and (4) to formulate the effectiveness of the innovation management and leadership training package. Research and Development Borg and Gall were used and combined with Dick & Carey's steps Instructional Design Modern. The study resulted in the package management and leadership training for Muhammadiyah, including training design, A Handbook for Facilitators, Handbook for Participants, and Module 3 Training Materials. Product Training Package has been validated by and trials on aspects of effectiveness and feasibility. The study also produced some impli-cations and recommendations relating to the training in the PTM (Muhammadiyah Higher Education).